Developing an integrated cadastre model of land and real estate in a single setting in Ukraine: key aspects and problems - Stupen, Nazar; Melnyk, Mariia (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
Many countries around the world have faced the challenge of creating 3D registrations within existing cadastral registries, which were designed to record the legal status of two-dimensional parcels. The key aspect of the 3D cadastre is the integration of 3D objects and land parcels within a single framework. This integration enables the determination of a 3D object's location relative to the surface level and specific areas on the surface. This article examines the main challenges and key aspects of developing one of the conceptual models of a 3D cadastre – an integrated model combining the 2D cadastre of land parcels with 3D real estate objects within a unified system (the so-called hybrid 3D cadastre model). The authors outline the major directions and prospects for the development of such a model. The introduction of a hybrid 3D cadastre model, as an intermediate stage in the transition to a fully developed 3D cadastre, is expected to facilitate the integration of Ukraine’s existing State Land Cadastre and registration system into European and global cadastral systems.